2018
DOI: 10.1186/s12936-018-2386-2
|View full text |Cite
|
Sign up to set email alerts
|

External quality assessment of malaria microscopy diagnosis in selected health facilities in Western Oromia, Ethiopia

Abstract: BackgroundAccurate early diagnosis and prompt treatment are one of the key strategies to control and prevent malaria disease. External quality assessment is the most effective method for evaluation of the quality of malaria microscopy diagnosis. The aim of this study was to assess the quality of malaria microscopy diagnosis and its associated factors in selected public health facility laboratories in East Wollega Zone, Western Ethiopia.MethodsFacility-based cross-sectional study design was conducted in 30 rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
3
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
6
16
3
5
Order By: Relevance
“…The mean test agreement in detecting malaria parasites in the present study (97.31%) was slightly higher than previous results from Amhara region of Ethiopia (96.6%) [11], and slightly lower than Pakistan (99.0-99.5%) [14]. On the other side the test agreement was significantly higher than recent results of 78, 88 and 91.7% from Oromia region of Ethiopia [15], Hawassa [16] and Addis Ababa [17], respectively. Variations in laboratory workload, training and assessment methods might bring the difference.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The mean test agreement in detecting malaria parasites in the present study (97.31%) was slightly higher than previous results from Amhara region of Ethiopia (96.6%) [11], and slightly lower than Pakistan (99.0-99.5%) [14]. On the other side the test agreement was significantly higher than recent results of 78, 88 and 91.7% from Oromia region of Ethiopia [15], Hawassa [16] and Addis Ababa [17], respectively. Variations in laboratory workload, training and assessment methods might bring the difference.…”
Section: Discussioncontrasting
confidence: 87%
“…Rate of false positive results (1.4%) was lower than previous findings of 2, 2.64 and 4.05%, 7.8, 24.6 and 24.4% from Canada [18], west Amhara, Ethiopia [11], Addis Ababa, Ethiopia [17], USA [19], Congo [20] and Oromia, Ethiopia [15], respectively. Similarly, frequency of false negative reporting was also low (1.3%) in the present study, implying that the overall performance of health facilities in malaria parasite detection is acceptably good.…”
Section: Discussioncontrasting
confidence: 69%
“…Therefore, laboratories should identify and report species correctly. The proportion of species mis-diagnosis in the present study (5.4%) goes in line with previous results of 3.4% in the same study area [12] and it is much lower than previous studies from Hawassa [15] and Oromia [14] where the laboratory professionals correctly identified the species in 74.3% and 44.6% of malaria positive slides during panel testing, respectively. The discrepancy might be due to difference in the method of assessment and the status of EQA and other supportive activities from reference laboratories.…”
Section: Discussionsupporting
confidence: 91%
“…The mean test agreement in detecting malaria parasites in the present study (97.31%) was in line with previous results from Amhara region of Ethiopia (96.6%) [12], and Pakistan (99.0-99.5%) [13]. On the other side the test agreement was higher than recent results of 78%, 88% and 91.7% from Oromia region of Ethiopia [14], Hawassa [15] and Addis Ababa [16], respectively. Variations in laboratory workload, training and assessment methods might bring the difference.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation